2015
DOI: 10.1093/mnras/stv2072
|View full text |Cite
|
Sign up to set email alerts
|

Forged in fire: cusps, cores and baryons in low-mass dwarf galaxies

Abstract: We present multiple ultra-high resolution cosmological hydrodynamic simulations of M 10 4−6.3 M dwarf galaxies that form within two M vir = 10 9.5−10 M dark matter halo initial conditions. Our simulations rely on the FIRE implementation of star formation feedback and were run with high enough force and mass resolution to directly resolve structure on the ∼ 200 pc scales. The resultant galaxies sit on the M vs. M vir relation required to match the Local Group stellar mass function via abundance matching. They h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
422
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 391 publications
(468 citation statements)
references
References 102 publications
43
422
3
Order By: Relevance
“…However, Hayashi & Chiba (2012) argued that the mass of the dSphs enclosed within inner 300 pc varies depending on their total luminosities, in contrast to the conclusion of Strigari et al (2008). Furthermore, recent high-resolution simulations (e.g., Di Cintio et al 2014a,b; Oñorbe et al 2015) imply that dark halo structures of classical-and UFD-like galaxies are generally different due to the effects of the stellar feedback energy associated with star formation history. Therefore, we believe that log L, log Vmax and log rmax of dSphs do not necessarily have a linear correlation but rather are independent quantities.…”
Section: The Difference In the Size Of The 1σ Uncertaintiesmentioning
confidence: 96%
“…However, Hayashi & Chiba (2012) argued that the mass of the dSphs enclosed within inner 300 pc varies depending on their total luminosities, in contrast to the conclusion of Strigari et al (2008). Furthermore, recent high-resolution simulations (e.g., Di Cintio et al 2014a,b; Oñorbe et al 2015) imply that dark halo structures of classical-and UFD-like galaxies are generally different due to the effects of the stellar feedback energy associated with star formation history. Therefore, we believe that log L, log Vmax and log rmax of dSphs do not necessarily have a linear correlation but rather are independent quantities.…”
Section: The Difference In the Size Of The 1σ Uncertaintiesmentioning
confidence: 96%
“…Recently, a number of studies (for example, Read & Gilmore 2005;Governato et al 2012;Di Cintio et al 2014;Chan et al 2015;Oñorbe et al 2015) have shown that including stellar feedback in simulations can significantly alter dwarf galaxies' density profiles, removing dark matter from the central regions and potentially reconciling the predictions of ΛCDM models with observations, at least for galaxies with M star =10 7−9.6 M e (M halo ≈10 10−11.5 M e ). We find similar dynamics for the stellar population, which is not surprising given that both stars and dark matter behave as Figure 9.…”
Section: Relation To Dark Matter Core-creationmentioning
confidence: 99%
“…At low redshifts the feedback effects have been proposed as the ones that have the major impact on the evolution of dwarf galaxies (see, e.g., Ferrara & Tolstoy 2000;Fujita et al 2004;Mashchenko et al 2008;Sawala et al 2011;Kawata et al 2014;Oñorbe et al 2015;Chen et al 2016;Papastergis & Shankar 2016). Our SHMR measurements, i.e., the higher than expected star formation efficiency, suggest that at z ∼ 3 a positive feedback effects have a significant influence on stellar mass assembly in not only dwarf galaxies (M < 10 9 ), like it is observed locally, but also in more massive ones, which at z = 0 are not observed to be strongly affected.…”
Section: The Stellar To Halo Mass Relation For Low Mass Galaxiesmentioning
confidence: 99%